Acoustic data during RV SONNE cruise SO287 - Ndague Diogoul; Birgit Quack (PANGAEA, 2025)
Acoustic data were recorded from December 12, 2021, to January 11, 2022, using a Simrad EK60 hull-mounted echosounder operating at four frequencies ( 18, 38 , 120, and 200 kHz) along the cruise track. The system operated continuously (24/7) with a 20 log R time-varied gain function, a pulse length of 1.024 ms, and a maximum transmission power of 2000 W. Data processing was conducted using the in-house software Matecho (Perrot et al., 2018) for echogram corrections, noise reduction, and extraction of fish schools and scattering layers (SSLs). Sound speed corrections were applied using temperature and salinity data from CTD measurements (Coly et al., 2022). The corrected data were echo-integrated at 0.1 nautical mile (nmi) intervals, and the Nautical Area Scattering Coefficient (NASC, m^2 nmi?^2) was used to assess spatial variability as a proxy for marine biomass. SSLs with mean volume backscattering strength (Sv) below -70 dB (relative micronektonic biomass) were extracted, and their descriptors were computed.